Evidence for Disruption of Normal Circadian Cortisol Rhythm in Women with Obesity - Al-Safi, Zain A (Gynecol Endocrinol, 2017)
Hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis may play a role in the pathogenesis of comorbidities encountered in obesity, including the relative hypogonadotropic hypogonadism that we and others have observed. We sought to examine serum cortisol profiles throughout the day and evening in a sample of normal weight women and women with obesity. In this cross-sectional study, regularly cycling obese (n=12) and normal weight (n=10) women were recruited. Mean serum cortisol was measured by frequent blood sampling for 16 hours (8am-midnight) in the luteal phase of the menstrual cycle. Women with obesity had significantly higher overall cortisol levels when compared to normal weight women (6.2 [4.3, 6.6] vs 4.7 [3.7, 5.5] ug/dl, p=0.04). Over the two-hour post-prandial period, obese women displayed an almost two-fold greater (7.2 [6.5, 8.6] ug/dl) rise in cortisol than normal weight controls (4.4 [3.7, 6.2] ug/dl, p<0.01). In addition, obese women demonstrated a sustained evening cortisol elevation compared to normal weight women, who displayed the typical decline in cortisol (3.2 [2.3, 4] vs 2 [1.5, 3.2] ug/dl, p<0.05). Changes in the HPA axis in the setting of obesity may be related to risks of obesity-associated metabolic comorbidities and reproductive dysfunction often seen in these women.